Eksistensi Laris Kartasura di Kalangan Mahasiswa: Penilaian Tiga Variabel Pendorong Keputusan Pembelian - Noor, Aisya; Naurah , Hasna Salwatun; Faturachman , Muhammad Syahrul; Solekhah , Liandawati (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This study aims to examine the influence of price perception, product completeness, and brand image on purchasing decisions. Each variable has several indicators, with one to two statements submitted in a questionnaire to respondents. Through data collection on the level of agreement of 105 students, the results were obtained to be analyzed using multiple linear regression techniques. Analysis of the price perception variable shows a significant influence of the variable on purchasing decisions. These results indicate that price is one of the factors that has a significant impact on students' decisions in making purchases at Laris, Kartasura. Analysis of other variables shows an influence but is not significant, namely on the product completeness and brand image variables. Both variables are tested to see how product variations in meeting heterogeneity of needs and positive brand image can be a major factor in consumer behavior in the form of purchases